THE ROLE OF INNOVATION IN INCREASING BUSINESS QUALITY AND THE ADDED VALUE FOR THE CUSTOMER - MIHAELA GHICAJANU; GABRIEL DOLEA (Annals of the University of Petrosani: Economics)
In today's business environments (regional, national or global) it is increasingly difficult for a company to differentiate from others and to create its own competitive advantages. If we think about it, most of what a company produces or sells can be bought from another company through a single Internet search. In order to be able to succeed and meet the demands and competitiveness of the market, or laws and rules that are constantly changing, companies need to reinvent themselves, or present something new, to rethink the business model. Under these conditions, business innovation can be a key element for increasing business quality and adding value to the customer. This paper will address those types of innovation that are closely related to the business redesign process, namely: product innovation, process innovation, organizational innovation and open innovation. These types of innovation are also the most common in business management theory and practice and in innovation management.